Diagnóstico de bacteriemia mediante técnicas microbiológicas y moleculares. - Baldeón Barragan, Karen María (2023)
The presence of bacteria in the bloodstream is known as bacteremia. Through a literature review, scientific information on the microbiological and molecular diagnosis of this condition was compiled. This research is descriptive, documentary, non-experimental, cross-sectional, and retrospective. Fifty scientific articles were reviewed, and 34 were selected according to the inclusion and exclusion criteria. The information was obtained from databases such as PubMed, Elsevier, Scielo, Lilacs, Dialnet, BVS Mediagraphic Regional Portal, Uniandes Magazine, IbnSina, InfoMed, and the Spanish Journal of Cardiology. With the analysis and discussion of different authors, the proposed objective was reached, showing that microorganisms such as E. coli, K. pneumoniae, A. baumannii, P. aeruginosa are the main causes of these infections. Age, prolonged hospitalization in intensive care units, comorbidities, previous use of antibiotics, and colonization by extended-spectrum β-lactamase-producing germs were found as risk factors associated with these pathologies. Conventional microbiological techniques are highlighted as the most used, along with molecular methods such as PCR, techniques based on the detection of nucleic acids, and mass spectrometry. The latter should be implemented in laboratories since they allow the rapid identification of the causative agents of this type of disease and detect resistance genes, significantly reducing the time to obtain results and improving patient care in terms of more appropriate and faster treatment.